Menemukan Harapan di Tengah Luka : Pendampingan Pastoral Bagi Ibu Butet Korban KDRT - Agustina Hutagalung; Ibelala Gea; Rogate Artaida Tiarasi Gultom (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Domestic violence (DV) is a phenomenon that significantly impacts the physical, psychological, and spiritual well-being of victims. This study aims to explore the role of pastoral counseling in assisting victims of domestic violence, specifically a woman named Ibu Butet, who experienced physical and psychological abuse from her husband and her husband’s family. A qualitative approach with a case study method was used to delve into Ibu Butet's experiences through empathetic pastoral interviews rooted in Christian spirituality. The pastoral care process focused on inner healing, discovering life’s meaning, and strengthening faith as a source of hope.The findings show that pastoral counseling provides a safe space for victims to express their emotional wounds, overcome trauma, and find new strength through spiritual reflection and prayer. In this context, the role of pastors or counselors as compassionate listeners embodying Christ’s love is crucial to the healing process. The study concludes that pastoral counseling not only helps victims cope with their suffering but also guides them to find renewed hope and purpose in life amidst difficult circumstances.